Estimating the role of three mesopredatory fishes in coral reef food webs at Ningaloo Reef, Western Australia - Thillainath, E.; McIlwain, Jennifer; Wilson, S.; Depczynski, M. (Springer, 2015)
Within the complex food webs that occur on coral reefs, mesopredatory fish consume small-bodied prey and transfer accumulated biomass to other trophic levels. We estimated biomass, growth and mortality rates of three common mesopredators from Ningaloo Reef in Western Australia to calculate their annual turnover rates and potential contribution to local trophic dynamics. Biomass estimates of the serranid Epinephelus rivulatus (4.46 ± 0.76 g m-2) were an order of magnitude greater than two smaller-bodied mesopredatory fishes, Pseudochromis fuscus (0.10 ± 0.03 g m-2) and Parapercis clathrata (0.23 ± 0.31 g m-2). Growth parameters generated from a von Bertalanffy growth function fitted to sizeat-age data, however, indicated that mortality rates for the three mesopredators were similar and that 32–55 % of fish survived each year. Consequently, interspecific differences in annual turnover rates among E. rivulatus (1.9 g m-2yr-1), Pa. clathrata (0.10 g m-2 yr-1) and Ps. fuscus (0.07 g m-2 yr-1) were an artefact of differences in local biomass estimates. The rapid turnover estimates for E. rivulatus suggest this species is an important conduit of energy within the isolated patch reef habitat where it is typically found, while Ps. fuscus and Pa. clathrata channel smaller amounts of energy from specific habitats in the Ningaloo lagoon. Apparent differences in habitat, diet and turnover rates of the three species examined provide an insight into the different roles these species play in coral reef food webs and suggest that life-history traits allow for variability in the local and spatial contribution of these species at Ningaloo Reef. Moreover, calculating turnover rates of a broader suite of fish species from a range of trophic groups will help better define the role of fishes in coral reef trophic dynamics.